Legal Punishment Problems in General Theory of Law: Array - Baltag, Dumitru; Dobinda, Vasile (Journal of Danubian Studies and Research, 2021)
The institution of legal punishment represents the institution that is emphasized in the article below. We have succeeded in making the comparison between the essence of notions such as: legal responsibility, legal sanction and that of legal punishment. It is thus explained that it would be good if the Theory of Law used the notion of “legal punishment” and not only the doctrine of criminal law. In the article below we thus present some points of view of remarkablepersonalities of the legal world on the benefits of the introduction of this thermal in the legal vocabulary.